2003
DOI: 10.1007/s00384-002-0470-z
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis and dendritic cell density are not correlated with metachronous distant metastasis in curatively operated rectal cancer

Abstract: Background and aims:Apart from surgery, treatment of rectal cancer increasingly involves the use of (neo-)adjuvant strategies. To optimize the selection process for these therapy regimens, especially in the field of cellular and molecular biology, new prognostic factors additional to the established TNM system are being investigated. Patients and methods: Two groups of patients (n=2×85) with rectal carcinoma curatively treated by surgery alone were studied retrospectively (median follow-up 6.1 years). To exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…There are a few conflicting reports in CRC regarding the clinicopathological significance of MVD, in which MVD is not associated with tumour stage [ 29 , 43 , 47 ], vascular and neural invasion [ 47 ], metastasis [ 29 ], or survival in the whole group of patients [ 4 , 29 , 48 , 49 ], subgroups of patients in stage A-C [ 47 ], or patients with stage I and II rectal cancer [ 50 ]. In addition, there were four studies which are performed on a small number of colon and/or rectal cancers (from 22 to 48 cases) that also show a non-association of MVD with the clinicopathological variables including tumour size, location, grade of differentiation, the presence of a mucinous component, stage, vascular or lymphovascular or neural invasion, or patient survival [ 30 , 51 - 53 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few conflicting reports in CRC regarding the clinicopathological significance of MVD, in which MVD is not associated with tumour stage [ 29 , 43 , 47 ], vascular and neural invasion [ 47 ], metastasis [ 29 ], or survival in the whole group of patients [ 4 , 29 , 48 , 49 ], subgroups of patients in stage A-C [ 47 ], or patients with stage I and II rectal cancer [ 50 ]. In addition, there were four studies which are performed on a small number of colon and/or rectal cancers (from 22 to 48 cases) that also show a non-association of MVD with the clinicopathological variables including tumour size, location, grade of differentiation, the presence of a mucinous component, stage, vascular or lymphovascular or neural invasion, or patient survival [ 30 , 51 - 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study in 170 patients with rectal cancer using CD1a as a marker for DCs did not find that DCs are related to survival [ 48 ]. Notably, Sandel et al ., using markers CD1a and CD208 for DCs in CRC, found that patients with high levels of either CD1a- or CD208-positive DCs had shorter survival [ 139 ].…”
Section: Introductionmentioning
confidence: 99%